Self-degrading organogel
By using the self-degrading gel formed by dibenzylidene sorbitol, the problems of insufficient blocking capacity of existing leak-blocking materials in large cracks and difficulty in degradation control are solved, effective sealing and self-degrading are achieved, and well drilling is improved Liquid plugging performance and oil production efficiency.
Patent Information
- Application Number
- CN202380035637.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2023-02-23
- Publication Date
- 2024-12-20
AI Technical Summary
The commonly used leak-blocking materials in existing drilling fluids have limited flow blocking capabilities in large cracks, and it is difficult to control the degradation time, which affects the efficiency of the drilling process and the later oil production capacity.
A self-degrading gel based on dibenzylidene sorbitol (DBS) was developed to control the sealing time and degradation process of the gel by reacting with solvents under acidic conditions.
The gel can effectively seal the cracks and degrade itself after a controlled period of time, reducing the impact on the drilling process and later oil production, and improving the reliability and efficiency of leak-blocking materials.
Smart Images

Figure BDA0005095980270000121 
Figure HDA0005095980280000011 
Figure HDA0005095980280000021
Abstract
Description
[0001] Overview
[0002] Oil and its products are an integral part of modern society. In order to obtain oil, oil wells need to be dug underground. During the drilling operation, a fluid called drilling fluid is circulated through the borehole. The drilling fluid facilitates the drilling process by bringing cuttings to the surface, providing well stability, and cooling and lubricating the drill bit. Lavrov, A., Lost circulation: Mechanisms and solutions, Gulf Professional Publishing, Elsevier (2016). However, if undesirable lateral fractures are present in the bedrock, they provide an escape path for the drilling fluid, which then leaks into the formation. This condition is called lost circulation and is one of the most serious, expensive, and time-consuming problems in drilling operations. Lavrov; Rabia, H., Oil well drilling engineering: Principles and practice, Graham & Trotman, London (1985).
[0003] To reduce fluid loss, one of the most common and widely used methods is to add solid particles to the drilling fluid. White, Robert J. Lost-circulation Materials and their Evaluation, Paper presented at the Drilling and Production Practice, New York, New York, January 1956. These particles can be anything from paper to chalk to food waste, and they are carried into the fractures by the fluid, where they accumulate and eventually seal the fractures. However, these traditional lost circulation materials (LCM) have limited flow blocking capabilities in large fractures. Boukadi, F., Yaghi, B., Al-Hadrami, H., Bemani, A., Babadagli, T., & De Mestre, P., "A Comparative Study of Lost Circulation Materials." Energy Sources, 26 (11), 1043–1051 (2004).
[0004] Compared to conventional methods, one or more embodiments of the present invention may involve more reliable gel-based LCMs. In addition to effective flow blocking, another important feature that one or more embodiments may exhibit is self-degradability. Since fractures play an important role in the oil recovery process, it is highly desirable to be able to degrade the LCM after the drilling operation is completed. Therefore, it is very important to design a material that can effectively plug fractures and degrade after a controlled period of time. The degradation time needs to be carefully controlled because the LCM needs to be an effective plugging agent that continues to be effective during the drilling process, but the time cannot be too long so as not to hinder the ability to recover oil during the production process.
[0005] A new type of LCM has been developed by converting oil-based fluids into gels. The food-grade compound dibenzylidene sorbitol (DBS) was found to convert oil-based fluids into gels via self-assembly. DBS was chosen because it is environmentally friendly, inexpensive compared to other low molecular weight gelling agents, and available in bulk from multiple suppliers. The gels formed by DBS are very strong and can effectively seal cracks. These gels are also degradable under acidic conditions. The degradation time can be controlled by the type and concentration of acid. Summary of the invention
[0006] The present disclosure provides a self-degrading gel composition comprising a liquid, a gelling agent, and a degradation agent, wherein the degradation agent degrades the gelling agent over time.
[0007] In some embodiments, the gelling agent is a low molecular weight compound.
[0008] In some embodiments, the gelling agent is dibenzylidene sorbitol (DBS), methyldibenzylidene sorbitol (methyl-DBS), dimethyldibenzylidene sorbitol (dimethyl-DBS), any other functional derivative of dibenzylidene sorbitol, or a combination thereof.
[0009] In some embodiments, the gelling agent is DBS.
[0010] In some embodiments, the concentration of the gelling agent is from about 0.25% to about 15% by weight.
[0011] In some embodiments, the concentration of the gelling agent is from about 0.25% to about 5% by weight.
[0012] In some embodiments, the concentration of the gelling agent is from about 2% to about 4% by weight.
[0013] In some embodiments, the concentration of the gelling agent is about 0.25% by weight.
[0014] In some embodiments, the concentration of the gelling agent is about 0.5% by weight.
[0015] In some embodiments, the concentration of the gelling agent is about 1% by weight.
[0016] In some embodiments, the concentration of the gelling agent is about 2% by weight.
[0017] In some embodiments, the concentration of the gelling agent is about 3% by weight.
[0018] In some embodiments, the concentration of the gelling agent is about 4% by weight.
[0019] In some embodiments, the degradation agent comprises one or more acids.
[0020] In some embodiments, the one or more acids are an inorganic acid, an organic acid, a Lewis acid, or a combination thereof.
[0021] In some embodiments, the inorganic acid is hydrochloric acid.
[0022] In some embodiments, the organic acid is butyric acid, hexanoic acid, octanoic acid, decanoic acid, dodecanoic acid, citric acid, formic acid, or a combination thereof.
[0023] In some embodiments, the Lewis acid is aluminum(III) chloride or bismuth(III) trifluoromethanesulfonate.
[0024] In some embodiments, the self-degrading gel composition further comprises a solvent.
[0025] In some embodiments, the solvent is dimethyl sulfoxide (DMSO), cyrene, dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), or a combination thereof.
[0026] In some embodiments, the solvent is DMSO.
[0027] In some embodiments, a portion of the DMSO is encapsulated within the wax particles.
[0028] In some embodiments, the liquid comprises an oil-based liquid or a water-based liquid.
[0029] In some embodiments, the oil-based liquid comprises mineral oil.
[0030] In some embodiments, the liquid further comprises hexanol, an organic acid, or a combination thereof.
[0031] In some embodiments, the liquid comprises from about 20% to about 80% by weight of mineral oil and from about 20% to about 80% by weight of hexanol, an organic acid, or a combination thereof.
[0032] In some embodiments, the liquid comprises from about 30% to about 50% by weight mineral oil and from about 30% to about 50% by weight hexanol.
[0033] The present disclosure also provides a method for preventing fluid loss in a rock formation, which comprises the following steps:
[0034] injecting a fluid into a borehole in the rock formation; and
[0035] A plugging material is injected into the borehole, wherein the plugging material comprises a gelling agent, which is a gel that plugs fractures or pore spaces in the rock formation.
[0036] In some embodiments, the loss occurs before, during, or after the drilling operation.
[0037] In some embodiments, the plugging material is a lost circulation material.
[0038] In some embodiments, the fluid is a drilling fluid.
[0039] In some embodiments, the gelling agent gel is a self-degrading gel that degrades over time.
[0040] In some embodiments, the gelling agent partially gels below the borehole to form a self-degrading gel.
[0041] In some embodiments, the gel is formed without heating.
[0042] In some embodiments, sealing of the fracture is reversible.
[0043] In some embodiments, the gel seals the fissure for about 1 day to 16 weeks.
[0044] In some embodiments, the gel seals the fissure for about 2 weeks to about 6 weeks.
[0045] In some embodiments, sealing of the fracture is reversed by degradation of the gel.
[0046] In some embodiments, the fractures or pore spaces contain oil, brine, or other reservoir fluids.
[0047] In some embodiments, sealing of the fracture prevents the fluid from contacting the reservoir fluid.
[0048] In some embodiments, the fluid is not in contact with the reservoir fluid.
[0049] In certain embodiments, the reservoir fluid is not contaminated by drilling fluid.
[0050] The present disclosure also provides a method of improving recovery of reservoir fluids in fractures or pore spaces, comprising plugging the fractures or pore spaces with the self-degradable gel composition described herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1is a photographic representation showing the addition of a concentrated dibenzylidene sorbitol (DBS) solution in DMSO (gelling solution) to a base oil followed by mixing to obtain a DBS gel.
[0052] Figure 2A is a line graph showing stress amplitude sweeps at 10 Hz for gels with different DBS concentrations.
[0053] Figure 2B is the elastic modulus (G') and yield stress (σ y ) versus the DBS concentration in the gel.
[0054] Figure 3A is a graph showing the pressure profile of the choke experiment described herein. The DBS concentration of the gel was 0.5 wt % and the inner diameter of the tube was 3 mm.
[0055] Figure 3B is a graph showing the maximum pressure that the plug can withstand as a function of the length of the plug. The DBS concentration of the gel is 0.5 wt %, and the inner diameter of the tube is 3 mm.
[0056] Figure 4A is a series of photographs showing that when pressure is applied, failure occurs at the interface and the plug moves along the wide tube (photo (i)); when there is a step change in tube diameter, the plug stops moving, and when the pressure is high enough, the plug enters the narrow tube (photo (ii)); and finally, the plug exits the flow loop (photo (iii)). The inner diameters of the wide and narrow tubes are 6.35 mm and 1.38 mm, respectively.
[0057] Figure 4B is a line graph showing the characteristic pressure distribution of the choke experiment described herein for a step change in tube diameter. The inner diameters of the wide and narrow tubes are 6.35 mm and 1.38 mm, respectively.
[0058] Figure 5 is a schematic diagram showing the degradation of DBS gel after four days of contact with aqueous hydrochloric acid. After four days, free oil and remaining gel are visible.
[0059] Figure 6 is a schematic diagram showing the synthesis of a self-degradable emulsion gel, in which an aqueous phase is dispersed in an oil phase and then gelled using DBS; due to the presence of acid in the aqueous phase, DBS slowly hydrolyzes and the gel eventually degrades.
[0060] Figure 7 is a set of two photographs showing the degradation of clear DBS gels over a few days due to the presence of organic acids (butyric acid, hexanoic acid or octanoic acid). The gels were made with mineral oil containing 20 wt% of organic acid. The DBS concentration in the gels was 0.5 wt% and the experiments were performed at 65°C.
[0061] Fig. 8A is a schematic diagram showing how DBS gel chemically degrades to ultimately form a dilute solution.
[0062] Figure 8B is a line graph showing the decrease in elastic modulus (G') over time as a DBS gel degrades. The gel contained 0.5 wt% DBS and 20 wt% caproic acid. The experiment was conducted at 65°C.
[0063] Fig. 9 is a graph showing the decrease in elastic modulus (G') over time as DBS gels degrade in the presence of C-8, C-10, C-6 or C-12 fatty acids.
[0064] Fig.10 Showing the degradation of DBS gel by contacting the gel with DMSO, including encapsulation of the DMSO in wax capsules, is a set of three photographs.
[0065] Fig.11 A schematic diagram showing the degradation of a DBS gel with bismuth (III) trifluoromethanesulfonate (BiTf) sprinkled on its surface (top), and a set of photographs showing the difference between a DBS gel not treated with BiTf (bottom left) and a DBS gel after treatment with BiTf for 12 hours (bottom right).
[0066] Fig.12 is a schematic diagram showing the degradation of DBS gel dispersed with aluminum (III) chloride (AlCl 3 ) (above), and a set of photographs showing the degradation of DBS gel dispersed with AlCl 3 at a temperature of 70° C. over six days.
[0067] Fig.13 is a scatter plot showing G' as a function of stress amplitude for gels having a DBS concentration of 0.25 wt%, 0.5 wt%, 1 wt%, 2 wt% or 5 wt% (A), and a scatter plot showing G' and σy as a function of DBS wt% (B).
[0068] Fig.14 is a series of scatter plots showing a stress sweep test (left), a step stress test (center), and a multiple-cycle step stress test (right) for a 1 wt % DBS gel in hexanol, all measured at a constant frequency of 10 Hz.
[0069] Fig.15 is a scatter plot showing the mass % of the DBS gel that remains intact over time after adding 0.3 M, 0.4 M, 0.5 M or 1 M hydrochloric acid (HCl) aqueous solution.
[0070] Fig.16is a schematic diagram showing the degradation of DBS gel over time (top) and a scatter plot showing the change in G' over time for DBS gels to which 0.2 M, 0.5 M or 1 M HCl was added.
[0071] Fig.17 A set of chemical structures showing the degradation of DBS in acid to form benzaldehyde and sorbitol (top), and a set of photographs showing the degradation of pure DBS over time in 2M HCl (bottom).
[0072] Fig.18 The infrared spectrum of the top oil layer of DBS degraded by HCl (left) and the infrared spectrum of the top oil layer of DBS degraded by HCl (right) 1 A set of line graphs of the H nuclear magnetic resonance (NMR) spectrum (right).
[0073] Fig.19 is a schematic diagram showing how a plugging material (e.g., the self-degrading gel described herein) is used to seal cracks in a borehole (top), and a set of photos showing how the self-degrading DBS gel (bottom layer in the left photo) blocks the flow of mineral oil (top layer in the left photo) for approximately 12 hours.
[0074] Fig. 20 is a graph showing the viscosity of DBS gel at 20°C as a function of shear rate.
[0075] Fig.21 is a graph showing the viscosity of DBS gel at 40°C as a function of shear rate.
[0076] Fig. 22 is a graph showing the viscosity of DBS gel at 70°C as a function of shear rate.
[0077] Fig.23 is a straight line graph showing the storage modulus of DBS gel as a function of DBS concentration in the gel.
[0078] Fig.24 is a graph showing the storage modulus of DBS gel as a function of octanoic acid concentration in the gel.
[0079] Fig.25 is a graph showing the storage modulus of DBS gel as a function of mud contaminant concentration.
[0080] Fig.26 is a line graph showing the decrease in storage modulus of a DBS gel at failure and subsequent recovery, which is repeated over multiple cycles.
[0081] Fig. 27 is a line graph showing the viscosity of DBS gel as a function of shear rate.
[0082] Fig.28 is a line graph showing the viscosity change over time of DBS gels formed at different shear rates. DETAILED DESCRIPTION
[0083] definition
[0084] Unless otherwise defined, all technical and scientific terms used herein have the meaning commonly understood by those skilled in the art to which the present disclosure belongs. In the event of a conflict, the present application, including the definitions, will prevail. Unless the context requires otherwise, singular terms shall include pluralities and plural terms shall include the singular.
[0085] Documents listed and / or cited in this disclosure are incorporated herein by reference, except for any statement that contradicts the express disclosure herein, except for a disclaimer or repudiation of subject matter, and except to the extent that the incorporated material is inconsistent with the express disclosure herein, in which case the language of the disclosure shall control.
[0086] Citation of any such document shall not be construed as an admission that the cited material is prior art to the present disclosure or as essential to the patentability of the present disclosure.
[0087] Although methods and materials similar or equivalent to those described herein can be used when implementing or testing the present disclosure, suitable methods and materials are described below. These materials, methods and examples are for illustrative purposes only and are not intended to be limiting. Other features and advantages of the present disclosure will be apparent from the detailed description and claims.
[0088] To further define the present disclosure, the following terms and definitions are provided.
[0089] Unless the context clearly dictates otherwise, the singular forms "a", "an", and "the" include plural references. The terms "a" (or "an"), "one or more", and "at least one" are used interchangeably herein. In some aspects, "a" or "an" means "single". In other aspects, "a" or "an" includes "two or more" or "plurality".
[0090] As used herein, the term "about" means approximately, about, in the vicinity of, or within the range of. When the term "about" is used in conjunction with a numerical range, it modifies that range by extending the boundaries above and below the numerical values recited. Generally, the term "about" as used herein is used to modify a numerical value by 10% above or below the stated value (up or down, higher or lower).
[0091] As used herein, the term "base oil" refers to the liquid to which the gelling solution is added to produce a gel. In addition to the above base oils, any liquid containing oil ("oil-based liquid") may be used, including oil-based liquids containing varying amounts of mineral oil and co-solvents (such as hexanol). Any liquid containing water ("water-based liquid") may also be used.
[0092] As used herein, the term "gelling agent" refers to any compound that forms a gel when subjected to a stimulus, including but not limited to the addition of a solvent or liquid, such as an oil-based liquid, an increase or decrease in temperature, or an increase or decrease in pressure.
[0093] As used herein, the term "gel" refers to a semisolid substance containing cross-linked materials. In some embodiments, the cross-links are covalent bonds. In some embodiments, the cross-links are hydrogen bonds. In some embodiments, the cross-links are intermolecular forces.
[0094] As used herein, the term "gelling solution" refers to a solution comprising a gelling agent.
[0095] As used herein, the term "mineral oil" refers to any mixture of higher alkanes from a mineral source, such as fractions of petroleum, including diesel, or similar synthetically derived mixtures, such as synthetic olefins (PAOs).
[0096] As used herein, the term "fluid" refers to any liquid whose flow may be slowed or stopped by a plugging material. As used herein, the term "plugging material" refers to any material that can be used to slow or stop the flow of a fluid. In certain embodiments, the fluid is water. In certain embodiments, the fluid is a drilling fluid. In certain embodiments, the plugging material is a self-degradable gel as described herein. In certain embodiments, the plugging material is used to slow or stop the flow of a fluid out of a borehole, such as a hole formed in a rock formation by drilling.
[0097] As used herein, the term "degradation agent" refers to any agent added to a gel that causes the gel to degrade into a liquid solution. In some embodiments, the degradation agent is an aqueous acid. In some embodiments, the degradation agent is a Lewis acid. In some embodiments, the degradation agent is a solvent.
[0098] Example Results and Discussion
[0099] Gel preparation without heating:
[0100] Typically, the preparation of low molecular weight gels requires heating to very high temperatures. However, heating the solvent requires high energy input and may not be feasible for large-scale industrial applications. Therefore, a method for synthesizing DBS gels that does not involve heating is used. In some embodiments, a high concentration of DBS (e.g., 15 wt%) is dissolved in dimethyl sulfoxide (DMSO) to produce a gel solution. A predetermined amount of this gel solution is then added to a base oil containing mineral oil and a co-solvent (hexanol). The mixture is then gently stirred and gelation occurs in less than a minute. Synthesis methods such as Figure 1 As shown. The co-solvent increases the compatibility of the solvent and helps to form a uniform gel. A base oil combination of 80 wt % mineral oil and 20 wt % hexanol was selected. The gels formed by conventional heating methods and non-heating methods were then compared using dynamic rheology. The results showed that there was no significant difference in the elastic modulus (G') of the two gels. Using a similar method, gels of other low molecular weight gelling agents or other derivatives of DBS (e.g., methyl DBS or dimethyl DBS) can also be synthesized. Other gelling agents other than DBS can be used.
[0101] Figure 1 A method for DBS gel synthesis without heating is shown. A concentrated solution of DBS in DMSO (gelling solution) is added to a base oil. After mixing, a firm DBS gel is obtained.
[0102] Effect of DBS concentration:
[0103] The viscoelastic properties of DBS gels were studied. The elastic (G') and viscous (G") moduli were measured as a function of gallant concentration. Fully developed gels were obtained at DBS concentrations as low as 0.25 wt%. These gels were identified using oscillatory shear rheology. In the gels, G' was generally higher than G", and G' was generally independent of the frequency range. All samples containing 0.25 wt% or higher DBS concentrations exhibited these gel properties. As shown by the increase in G' values ( Figure 2A ), as the strength of the gel increases with the increase of DBS concentration. Figure 2B The relationship between G' and gelator concentration is shown, as well as a power law relationship with exponent n = 2. Fig.23 As shown in Figure 2, the increase in gel strength with increasing DBS concentration was also observed by examining the storage modulus in the linear viscoelastic (LVE) region. Fig.24As shown, the strength of the gel can also be changed by adjusting the concentration of the organic acid. Since these gels are assembled through weak intermolecular interactions, the gels exhibit thixotropic behavior. When high stress amplitudes (above the yield stress) are applied, the gels behave like liquids. Figure 2A It is shown that G' is constant when low stress is applied. Once the yield stress value is exceeded, a rapid decrease in G' is observed. Figure 2B It is shown that the yield stress increases with the increase of gelling agent concentration. The yield stress and gelling agent concentration also have a power law relationship with exponent n=1.3.
[0104] Figure 2 shows the relationship between the viscoelastic properties of the gel and the DBS concentration. A) shows the stress amplitude sweep at 10 Hz for gels with different DBS concentrations. B) shows the relationship between the elastic modulus (G') and the yield stress (σy) as a function of the DBS concentration in the gel.
[0105] DBS gels also exhibit shear thinning and thixotropy. That is, the nanofiber network of DBS is connected by weak bonds, and these weak bonds are broken by shear forces. This causes the sample to liquefy under shear force, while the viscosity decreases with increasing shear rate. When the shear force stops, the network quickly recovers and the gel regains its elastic (solid) properties. These aspects are Fig.14 As shown, this figure is the data for 1% DBS gel in hexanol.
[0106] Fig.14 (A) (left) is a graph of the elastic modulus G' and viscous modulus G" as a function of stress amplitude. At low stress, G'~40,000Pa is constant, indicating that the DBS network is intact. But when the yield stress σy (~200Pa) is exceeded, G' decreases rapidly, indicating that the network is destroyed, that is, the sample is converted into a liquid.
[0107] Fig.14 (B) (center) shows the results of the above samples in a step stress test. At low stress (10Pa), the gel is intact (G'>G"). In the second step, a stress of 300Pa (>σy) is applied, which destroys the network and the rheology becomes liquid-like (G">G'). In the final step, the stress is reduced back to 10Pa and the gel state is quickly restored (in <20s). The rapid recovery of the DBS network is also seen in repeated cycles of the step stress test ( Fig.14 (C) (right). Even after 10 such cycles, the gel modulus G' barely changes.
[0108] The rheology of DBS gels was also studied as a function of DBS concentration. Fig.13As shown in Figure 2, both the gel modulus G' and the yield stress σy increase steadily with the increase of DBS. The log-log plots of G' and σy versus DBS concentration c show that both quantities obey the polymer law ( Fig.13 (below)), where G~c 2 , and σy~c 1.3 .
[0109] These gels also maintain their strength over a wide temperature range, for example, from about 10°C to about 90°C or from about 20°C to about 70°C. Figure 20-22 As shown, at 20 °C, 40 °C, and 70 °C, the viscosity of DBS gel decreases with increasing shear rate but recovers quickly after the shear rate is reversed, indicating that it has strength over a wide temperature range.
[0110] Gels may also be self-healing. As used herein, the term "self-healing" refers to the ability of a gel that has lost its initial strength (e.g., as measured by viscosity) to spontaneously recover its initial strength (or a significant percentage thereof). Fig.26 As shown, the DBS gel exhibited self-healing properties, in which the DBS gel was destroyed and able to reform multiple times.
[0111] It was also found that the shear rate during gel formation affects the gel viscosity. Fig.28 As shown, the gel formed at a lower shear rate is much more viscous than the gel formed at a higher shear rate.
[0112] Gel blocking ability:
[0113] To better understand the plugging ability of the gel, a plugging experiment was performed. A 0.5 wt% DBS gel was used to plug a smooth plastic tube. Then, water was pumped in and the pressure required to break the plug and restore flow was measured. Figure 3A Characteristic pressure curves are shown. The plug failure occurs at the interface between the gel and the smooth plastic tube. The gel plug does not deform or move along the length of the tube due to water pressure. The plug length varies, and increasing the plug length is observed to increase the failure pressure ( Figure 3B ).
[0114] Figure 3 shows the plugging of a smooth plastic tube with DBS gel. A) shows the characteristic pressure curve of the flow blocking experiment. B) shows the maximum pressure that the plug can withstand as a function of the length of the plug. The DBS concentration of the gel is 0.5% by weight and the inner diameter of the tube is 3 mm.
[0115] To simulate cracks in rock formations (the diameter of these cracks is not constant), two plastic tubes of different diameters were connected together ( Figure 4A). The plug is placed in the larger diameter tube and water is pumped in. As before, failure occurs at the interface. Once the plug reaches the mouth of the narrower tube, it stops and the pressure continues to increase. Eventually, the gel deforms and enters the narrower tube. The gel then takes on a cylindrical shape with a diameter equal to the inner diameter of the narrow tube. The gel then moves along the tube and exits the tube as a cylindrical plug. The characteristic pressure curve for this flow experiment is shown in Figure 1. Figure 4B The pressure required to deform the gel is much higher than the pressure that causes the interface between the gel and the smooth tube to fail.
[0116] Figure 4 shows a flow control experiment with a step change in pipe diameter. A) (i) When pressure is applied, failure occurs at the interface and the plug moves along the wide pipe. (ii) When the pipe diameter changes step-wise, the plug stops moving. When the pressure is high enough, the plug moves into the narrow pipe. (iii) Eventually, the plug exits the flow loop. B) Characteristic pressure distribution of a flow control experiment with a step change in pipe diameter. The inner diameters of the wide and narrow pipes are 6.35 mm and 1.38 mm, respectively.
[0117] In some embodiments, the gel can seal cracks or pore spaces in the rock formation. In some embodiments, the seal is reversible. In some embodiments, the seal is reversed by degradation of the gel after a period of time. By changing various aspects of the gel, including but not limited to the concentration of the gelling agent, degradation agent, or gelling agent and / or degradation agent, the length of the time period before the seal is reversed by degradation can be controlled. The degradation of the gel can be carried out by various methods described herein.
[0118] In some embodiments, the gel seals the cracks or pore spaces for about 1 day to 4 weeks. In some embodiments, the gel seals the cracks or pore spaces for about 2 weeks to 6 weeks. In some embodiments, the gel seals the cracks or pore spaces for about 1 day to about 2 days, about 1 day to about 3 days, about 1 day to about 4 days, about 1 day to about 5 days, about 1 day to about 6 days, about 1 day to about 1 week, about 1 day to about 2 weeks, about 1 day to about 3 weeks, about 2 days to about 3 days, about 2 days to about 3 days, about 2 days to about 4 days, about 2 days to about 5 days, about 2 days to about 6 days, about 2 days to about 1 week, about 2 days to about 2 weeks, about 2 days to about 3 weeks, about 2 days to about 4 weeks, about 3 days to about 4 days, about 3 days to about 5 days, about 3 days to about 6 days, about 3 days to about 1 week, about 3 ... days, about 3 days to about 5 days, about 3 days to about 6 days, about 3 days to about 1 week, about 3 days to about 2 weeks or about 1 week to about 2 weeks, about 3 days to about 3 weeks, about 3 days to about 4 weeks, about 4 days to about 5 days, about 4 days to about 6 days, about 4 days to about 1 week, about 4 days to about 2 weeks, about 4 days to about 3 weeks, about 4 days to about 4 weeks, about 5 days to about 6 days, about 5 days to about 1 week, about 5 days to about 2 weeks, about 5 days to about 3 weeks, about 5 days to about 4 weeks, about 6 days to about 1 week, about 6 days to about 2 weeks, about 6 days to about 3 weeks, about 6 days to about 4 weeks, about 1 week to about 2 weeks, about 1 week to about 3 weeks, about 1 week to about 4 weeks, about 2 weeks to about 3 weeks, about 2 weeks to about 4 weeks, or about 3 weeks to about 4 weeks.In some embodiments, the gel seals cracks or pore spaces for about 2 weeks to about 5 weeks, about 2 weeks to about 6 weeks, about 2 weeks to about 7 weeks, about 2 weeks to about 8 weeks, about 2 weeks to about 9 weeks, about 2 weeks to about 10 weeks, about 2 weeks to about 11 weeks, about 2 weeks to about 12 weeks, about 2 weeks to about 13 weeks, about 2 weeks to about 14 weeks, about 2 weeks to about 15 weeks, about 2 weeks to about 16 weeks, about 3 weeks to about 5 weeks, about 3 weeks to about 6 weeks, about 3 weeks to about 7 weeks, about 3 weeks to about 8 weeks, about 3 weeks to about 9 weeks, about 3 weeks to about 10 weeks, about 3 weeks to about 11 weeks, about 3 weeks to about 12 weeks, about 3 weeks to about 13 weeks, about 3 weeks to about 14 weeks, about 3 weeks to about 15 weeks, about 3 weeks to about 16 weeks, about 4 weeks to about 5 weeks , about 4 weeks to about 6 weeks, about 4 weeks to about 7 weeks, about 4 weeks to about 8 weeks, about 4 weeks to about 9 weeks, about 4 weeks to about 10 weeks, about 4 weeks to about 11 weeks, about 4 weeks to about 12 weeks, about 4 weeks to about 13 weeks, about 4 weeks to about 14 weeks, about 4 weeks to about 15 weeks, about 4 weeks to about 16 weeks, about 5 weeks to about 6 weeks, about 5 weeks to about 7 weeks, about 5 weeks to about 8 weeks, about 5 weeks to about 9 weeks, about 5 weeks to about 10 weeks, about 5 weeks to about 11 weeks, about 5 weeks to about 12 weeks, about 5 weeks to about 13 weeks, about 4 weeks to about 14 weeks, about 5 weeks to about 15 weeks, about 4 weeks to about 16 weeks, about 5 weeks to about 6 weeks, about 5 weeks to about 7 weeks, about 6 weeks to about 8 weeks, about 6 weeks to about 9 weeks, about 6 weeks to about 10 weeks, about 6 weeks to about 11 weeks, about 6 weeks to about 12 weeks, about 6 weeks to about 13 weeks, about 6 weeks to about 14 weeks, about 6 weeks to about 15 weeks, about 6 weeks to about 16 weeks, about 7 weeks to about 8 weeks, about 7 weeks to about 9 weeks, about 7 weeks to about 10 weeks, about 7 weeks to about 11 weeks, about 7 weeks to about 12 weeks, about 7 weeks to about 13 weeks, about 7 weeks to about 14 weeks, about 7 weeks to about 15 weeks, about 7 weeks to about 16 weeks, about 8 weeks to about 9 weeks, about 8 weeks to about 10 weeks, about 8 weeks to about 11 weeks, about 8 weeks to about 12 weeks, about 8 weeks to about 13 weeks, about 8 weeks to about 14 weeks, about 8 weeks to about 15 weeks, about 8 weeks to about 16 weeks, about 9 weeks to about 10 weeks, about 9 weeks to about 11 weeks, about 9 weeks to about 12 weeks, about 9 weeks to about 13 weeks, about 9 weeks From about 1 week to about 14 weeks, from about 9 weeks to about 15 weeks, from about 9 weeks to about 16 weeks, from about 10 weeks to about 11 weeks, from about 10 weeks to about 12 weeks, from about 10 weeks to about 13 weeks, from about 10 weeks to about 14 weeks, from about 10 weeks to about 15 weeks, from about 10 weeks to about 16 weeks, from about 11 weeks to about 12 weeks, from about 11 weeks to about 13 weeks, from about 11 weeks to about 14 weeks, from about 11 weeks to about 15 weeks, from about 11 weeks to about 16 weeks, from about 12 weeks to about 13 weeks, from about 12 weeks to about 14 weeks, from about 12 weeks to about 15 weeks, from about 12 weeks to about 16 weeks, from about 13 weeks to about 14 weeks, from about 13 weeks to about 15 weeks, from about 13 weeks to about 16 weeks, from about 14 weeks to about 15 weeks, from about 14 weeks to about 16 weeks, or from about 15 weeks to about 16 weeks.
[0119] In some embodiments, the gel plugs the cracks or pore spaces for about 1 day. In some embodiments, the gel plugs the cracks for about 2 days, about 3 days, about 4 days, about 5 days, about 9 days, about 1 week, about 2 weeks, about 3 weeks, or about 4 weeks. In some embodiments, the gel plugs the cracks or pore spaces for about 5 weeks, about 6 weeks, about 7 weeks, about 8 weeks, about 9 weeks, about 10 weeks, about 11 weeks, about 12 weeks, about 13 weeks, about 14 weeks, about 15 weeks, or about 16 weeks.
[0120] Self-degradable gel:
[0121] DBS gels are formed by weak intermolecular forces, so the gel can be degraded by solvents that can dissolve DBS. When DBS gels are in contact with DMSO (DMSO is a good solvent for DBS), the gel will degrade. DBS partitions from the gel into DMSO, and the gel is eventually physically degraded. In other embodiments, the gel is chemically degraded. It has also been found that DBS gels degrade in the presence of acid. Figure 5 It was shown that when an aqueous solution of hydrochloric acid (HCl) was brought into contact with a DBS gel, the gel began to degrade and was completely degraded within a few days. DBS contains two acetal groups, which react with the acid to form an aldehyde. Therefore, without wishing to be bound by theory, it is assumed that in the presence of an acid, DBS chemically hydrolyzes to benzaldehyde and sorbitol according to the following reaction scheme:
[0122]
[0123] The degradation products, benzaldehyde and sorbitol, do not have self-assembly properties, so after DBS hydrolysis, the gel is converted into a dilute solution. Tollens' Test was performed on the samples before and after acid degradation. The results showed that aldehydes were produced after degradation, supporting the above hypothesis.
[0124] Figure 5 The degradation of DBS gel in the presence of aqueous acid is shown. When DBS gel is in contact with aqueous HCl, the gel begins to degrade and eventually degrades completely within a few days. After 4 days, free oil and remaining gel are visible.
[0125] Since acid degradation is a relatively slow process, a gel can be synthesized with acid already present in it. Due to the slow degradation, the resulting gel can be stable for several days, but will eventually degrade into a dilute solution. To prepare a self-degrading gel, a water-in-oil emulsion is formed. A mineral oil-hexanol mixture is used as the oil phase, and hydrochloric acid (HCl) of the desired concentration is used as the water phase. Then, the gelling solution is quickly added to form an emulsion gel. The process is as follows Figure 6 These latex gels exhibited self-degradation behavior, and the degradation time depended on the acid concentration.
[0126] Figure 6 The synthesis of a self-degradable emulsion gel is schematically shown. The aqueous phase is dispersed in the oil phase and then gelled using DBS. Due to the presence of acid, DBS slowly hydrolyzes and eventually degrades the gel.
[0127] It is observed that the degradation time of self-degradable emulsion gels decreases with the increase of acid concentration. It is also found that the degradation time of weak acids (such as formic acid) is longer than that of emulsion gels using HCl of the same concentration. In an example, the concentration of hydronium ions determines the degradation time. Since weak acids do not completely dissociate, a higher concentration of acid is required to achieve a degradation time similar to that of gels using strong acids. Therefore, the degradation time of these self-degradable emulsion gels can be controlled by the type and concentration of the acid used. In some embodiments, one or more acids, such as one or more, two or more, three or more or four or more acids are used to degrade the gel.
[0128] In some embodiments, the gel degrades over a period of about 1 day to about 4 weeks. In some embodiments, the gel degrades over a period of about 2 weeks to about 6 weeks. In some embodiments, the gel degrades over a period of about 1 day to about 2 days, about 1 day to about 3 days, about 1 day to about 4 days, about 1 day to about 5 days, about 1 day to about 6 days, about 1 day to about 1 week, about 1 day to about 2 weeks, about 1 day to about 3 weeks, about 2 days to about 3 days, about 2 days to about 4 days, about 2 days to about 5 days, about 2 days to about 6 days, about 2 days to about 1 week, about 2 days to about 2 weeks, about 2 days to about 3 weeks, about 2 days to about 4 weeks, about 3 days to about 4 days, about 3 days to about 5 days, about 3 days to about 6 days, about 3 days to about 1 week, about 3 days to about 2 weeks, about 3 days to about In some embodiments, the present invention relates to a method for degrading an organic compound in an organic compound or an organic compound. The organic compound may be present in an organic compound or an organic compound that is ...In some embodiments, the gel lasts from about 2 weeks to about 5 weeks, from about 2 weeks to about 6 weeks, from about 2 weeks to about 7 weeks, from about 2 weeks to about 8 weeks, from about 2 weeks to about 9 weeks, from about 2 weeks to about 10 weeks, from about 2 weeks to about 11 weeks, from about 2 weeks to about 12 weeks, from about 2 weeks to about 13 weeks, from about 2 weeks to about 14 weeks, from about 2 weeks to about 15 weeks, from about 2 weeks to about 16 weeks, from about 3 weeks to about 5 weeks, from about 3 weeks to about 6 weeks, from about 3 weeks to about 7 weeks, from about 3 weeks to about 8 weeks, from about 3 weeks to about 9 weeks, from about 3 weeks to about 10 weeks, from about 3 weeks to about 11 weeks, from about 3 weeks to about 12 weeks, from about 3 weeks to about 13 weeks, from about 3 weeks to about 14 weeks, from about 3 weeks to about 15 weeks, from about 3 weeks to about 16 weeks, from about 4 weeks to about 5 weeks, from about 4 weeks to about 6 weeks. , about 4 weeks to about 7 weeks, about 4 weeks to about 8 weeks, about 4 weeks to about 9 weeks, about 4 weeks to about 10 weeks, about 4 weeks to about 11 weeks, about 4 weeks to about 12 weeks, about 4 weeks to about 13 weeks, about 4 weeks to about 14 weeks, about 4 weeks to about 15 weeks, about 4 weeks to about 16 weeks, about 5 weeks to about 6 weeks, about 5 weeks to about 7 weeks, about 5 weeks to about 8 weeks, about 5 weeks to about 9 weeks, about 5 weeks to about 10 weeks, about 5 weeks to about 11 weeks, about 5 weeks to about 12 weeks, about 5 weeks to about 13 weeks, about 5 weeks to about 14 weeks, about 5 weeks to about 15 weeks, about 5 weeks to about 16 weeks, about 6 weeks to about 7 weeks, about 6 weeks to about 8 weeks, about 6 weeks to about 9 weeks, about 6 weeks to about 10 weeks, about 6 weeks to about 11 weeks, about 6 weeks to about 12 weeks , about 6 weeks to about 13 weeks, about 6 weeks to about 14 weeks, about 6 weeks to about 15 weeks, about 6 weeks to about 16 weeks, about 7 weeks to about 8 weeks, about 7 weeks to about 9 weeks, about 7 weeks to about 10 weeks, about 7 weeks to about 11 weeks, about 7 weeks to about 12 weeks, about 7 weeks to about 13 weeks, about 7 weeks to about 14 weeks, about 7 weeks to about 15 weeks, about 7 weeks to about 16 weeks, about 8 weeks to about 9 weeks, about 8 weeks to about 10 weeks, about 8 weeks to about 11 weeks, about 8 weeks to about 12 weeks, about 8 weeks to about 13 weeks, about 8 weeks to about 14 weeks, about 8 weeks to about 15 weeks, about 8 weeks to about 16 weeks, about 9 weeks to about 10 weeks, about 9 weeks to about 11 weeks, about 9 weeks to about 12 weeks, about 9 weeks to about 13 weeks, about 9 weeks to about 14 weeks, about The invention also relates to a method for degrading an enzyme in a pharmaceutical composition or an enzyme that degrades in an amount of about 9 weeks to about 15 weeks, about 9 weeks to about 16 weeks, about 10 weeks to about 11 weeks, about 10 weeks to about 12 weeks, about 10 weeks to about 13 weeks, about 10 weeks to about 14 weeks, about 10 weeks to about 15 weeks, about 10 weeks to about 16 weeks, about 11 weeks to about 12 weeks, about 11 weeks to about 13 weeks, about 11 weeks to about 14 weeks, about 11 weeks to about 15 weeks, about 11 weeks to about 16 weeks, about 12 weeks to about 13 weeks, about 12 weeks to about 14 weeks, about 12 weeks to about 15 weeks, about 12 weeks to about 16 weeks, about 13 weeks to about 14 weeks, about 13 weeks to about 15 weeks, about 13 weeks to about 16 weeks, about 14 weeks to about 15 weeks, about 14 weeks to about 16 weeks, or about 15 weeks to about 16 weeks.
[0129] In some embodiments, the gel degrades within about 1 day. In some embodiments, the gel degrades within about 2 days, about 3 days, about 4 days, about 5 days, about 9 days, about 1 week, about 2 weeks, about 3 weeks, or about 4 weeks. In some embodiments, the gel degrades within about 5 weeks, about 6 weeks, about 7 weeks, about 8 weeks, about 9 weeks, about 10 weeks, about 11 weeks, about 12 weeks, about 13 weeks, about 14 weeks, about 15 weeks, or about 16 weeks.
[0130] The degradation time can be easily adjusted by various parameters including but not limited to acid content and temperature. The higher the acid concentration or temperature, the faster the degradation rate. The effect of acid content (i.e. [HCl]) was studied, such as Fig.15 and 16 As shown. Gels of 2% DBS in 80 / 20 PEG / acid solution were prepared, with the molar concentration of the acid varying from 0.2 to 1 M. In all cases, the gels were incubated at 30°C and the mass fraction of intact gel, m, was measured over time. gel (Coexisting with sol). Fig.15 Display, m gel It drops to zero in a few days, and the higher the acid content, the faster the drop. All curves show an inverse-sigmoidal shape. gel Changes slowly, then drops sharply, and finally approaches zero. Degradation time t degr It can be defined as the time for the gel to be completely degraded (i.e., m gel = 0) or the time at the midpoint of the S-shaped curve (i.e. m gel =50%). In either case, t degr As [HCl] increases, t decreases. For example, if [HCl] = 0.3 M in the aqueous phase, t degr (m gel =0) is 10 days, and if [HCl] = 1 M, t degr (m gel =0) is only 3 days.
[0131] The rheology of the intact gel portion during gel degradation in the above experiments was also studied. Fig.16 As shown in (below), the modulus G' of the intact gel was measured over time. It was found that G' decayed exponentially with time t (to reveal the exponential nature of the decay, the data were presented as a semi-logarithmic plot of G' vs. t, with the data falling on a straight line). In addition, the higher the hydrochloric acid concentration [HCl], the faster the decay of G', i.e., the higher the slope in the semi-logarithmic plot.
[0132] In order to clarify the reaction mechanism, Fig.17(below) is the experiment shown. 5 grams of solid DBS powder was placed on top of 5 grams of 2M HCl aqueous solution and left at 70°C. Over time (about 48 hours), all the solids disappeared, leaving two liquid phases: an oil phase on the top and an aqueous phase on the bottom. The top phase was examined using Fourier transform infrared (FTIR) spectroscopy. The carbonyl (C=O) peak was clearly seen in the spectrum, as shown in Figure 1. Fig.18 (Left) Both DBS and HCl aqueous solutions do not contain carbonyl groups, indicating that the carbonyl groups come from the reaction products.
[0133] The top phase was further examined using nuclear magnetic resonance (NMR) spectroscopy. From the NMR spectrum ( Fig.18 , right) confirmed the presence of benzaldehyde, a molecule containing a carbonyl group (C=O). This helps to clarify the reaction between DBS and acid. The DBS molecule contains an acetal group (see Fig.17 Structure on the upper left). In organic synthesis, acetals are often used as protecting groups because they are stable to strong bases and nucleophiles but hydrolyze under acidic conditions. Without being bound by theory, it is believed that DBS is likely hydrolyzed by acid to form benzaldehyde and sorbitol, such as Fig.17 (above) is the reaction scheme. Sorbitol does not appear in the NMR spectrum because it is hydrophilic and therefore may be assigned to Fig.17 (Bottom right) In the aqueous phase shown, neither benzaldehyde nor sorbitol can self-assemble into nanofibers, which explains why the gel degrades.
[0134] Further findings showed that DBS gels can be degraded under anhydrous conditions. If pure organic acids are added to the DBS gel, it still degrades. There are two advantages to using organic acids compared to emulsion gels. First, the gel formed is uniform, and second, using organic acids eliminates the need for a cosolvent. Since the organic acid can be directly dissolved in the oil phase, the system is single-phase. This is useful because for a two-phase system, a consistent preparation method is beneficial because the emulsion droplets may have a significant impact on the gel strength and degradation time. In addition, long-chain aliphatic organic acids are directly soluble in mineral oil. Organic acids can act as both degradation agents and cosolvents. Therefore, self-degradable organogels can be easily prepared with fewer components. As with emulsion gels, the degradation time decreases as the acid concentration increases. The type of organic acid may also have an impact on the degradation time. Figure 7 The results show that the gel using butyric acid degraded faster than the gel using caproic acid, which in turn degraded faster than the gel using caprylic acid. In this experiment, the mass concentration of each acid was the same (20 wt%), which means that the molar concentration of long-chain fatty acids was lower, which may be the reason for the slower degradation rate.
[0135] Figure 7Self-degradable organogels are shown. The figure shows that a clear DBS gel degrades in a few days due to the presence of organic acids. The gel is made of mineral oil containing 20 wt% organic acid. The DBS concentration in the gel is 0.5 wt% and the experiment was performed at 65°C.
[0136] The elastic modulus G' of the self-degradable organogels was also measured over time. As expected, the G' value decreased over time due to the degradation of DBS. Fig. 8A A schematic showing the concept of a self-degradable organogel. Depending on the type and concentration of the acid, the lifetime of the gel can be controlled. Figure 8B The G' value of a DBS gel containing 20 wt% hexanoic acid was shown to decrease over a week. DBS gels can also be degraded in the presence of solid Lewis acids such as AlCl3. Therefore, self-degradable organogels can be prepared by dispersing solid acid particles in the gel. Through the incorporation of acids, the synthesis method of self-degradable organogels as new plugging materials has been demonstrated. Since this material can also effectively plug leaks outside of drilling, it can also be more broadly referred to as a "plugging material". The same concept can also be achieved with various DBS derivatives such as methyl DBS or dimethyl DBS.
[0137] In some embodiments, the plugging material can be used as a plugging agent in a subterranean application. In some embodiments, the subterranean application is completion, remediation, intervention, or production.
[0138] Plugging materials can also be used to improve the recovery of reservoir fluids from fractures or pores in rock formations. When plugged by plugging materials, reservoir fluids may become trapped in fractures or pores. Once the plugging materials degrade, these fluids can be recovered. In contrast, if irreversible / non-degradable plugging materials are used, these fluids are unlikely to be recovered.
[0139] Figure 8 shows the concept of self-degrading gel. A) In the presence of acid, DBS undergoes chemical degradation. Eventually, the gel converts to a dilute solution. B) As DBS degrades, the elastic modulus of the gel decreases. The G' value of a gel containing 0.5 wt% DBS and 20 wt% hexanoic acid is shown. The experiment was performed at 65°C.
[0140] The degradation rate of DBS gel is a function of the type of acid, acid concentration, and temperature. Through systematic experiments, the relationship between the degradation rate and the above variables can be studied. Based on these "formulas", the degradation time can be adjusted. For example, to ensure that the gel degrades after 7 days at a temperature of 65°C, the formula described in this article may suggest the use of a specific organic acid (such as hexanoic acid) at a specific concentration. Preliminary results show that DBS gels will also degrade in the presence of solid Lewis acids (such as aluminum chloride). Degradation using environmentally friendly particulate Lewis acids dispersed in the gel can also be studied. Rheological experiments can also be performed to obtain a plot of G' changing with time. Rheological studies can also be correlated with flow blocking experiments. That is, DBS gels can be designed to be strong enough to block flow.
[0141] In some embodiments, a Lewis acid acts as a catalyst. Fig.11 As shown, the addition of a Lewis acid (e.g., bismuth (III) trifluoromethanesulfonate) can accelerate the degradation of DBS gels. In some embodiments, the Lewis acid is aluminum (III) chloride or bismuth (III) trifluoromethanesulfonate. Other Lewis acids are known to those skilled in the art.
[0142] In addition, a similar strategy can also be used for gelling water. Low molecular weight gelators including DBS can form good hydrogels with co-solvents. Therefore, this method can be extended to prepare self-degradable water-based gels.
[0143] In addition to DMSO, other solvents may be used to form gels, including but not limited to cyrene, dimethylformamide (DMF), and N-methyl-2-pyrrolidone (NMP).
[0144] The concentration of the various components of the self-degradable gel can vary. In some embodiments, the concentration of the gel is from about 2% to about 4% by weight. In some embodiments, the concentration of the gel is from about 0.25% to about 15% by weight, from about 1% to about 10% by weight, from about 2% to about 8% by weight, or from about 3% to about 5% by weight.
[0145] In some embodiments, the concentration of the gel is about 2 weight %. In some embodiments, the concentration of the gel is about 0.25 weight %, about 0.5 weight %, about 0.75 weight %, about 1 weight %, about 2 weight %, about 3 weight %, about 4 weight %, about 5 weight %, about 6 weight %, about 7 weight %, about 8 weight %, about 9 weight %, about 10 weight %, about 11 weight %, about 12 weight %, about 13 weight %, about 14 weight % or about 15 weight %.
[0146] In some embodiments, the concentration of mineral oil is from about 20% to about 80% by weight, from about 30% to about 80% by weight, from about 40% to about 80% by weight, from about 50% to about 80% by weight, from about 60% to about 80% by weight, from about 70% to about 80% by weight, from about 20% to about 70% by weight, from about 30% to about 70% by weight, from about 40% to about 70% by weight, from about 50% to about 70% by weight, from about 60% to about 70% by weight, from about 20% to about 60% by weight, from about 30% to about 60% by weight, from about 40% to about 60% by weight, from about 50% to about 60% by weight, from about 20% to about 50% by weight, from about 30% to about 50% by weight, from about 40% to about 50% by weight, from about 20% to about 40% by weight, or from about 20% to about 30% by weight.
[0147] In some embodiments, the concentration of mineral oil is about 50% by weight. In some embodiments, the concentration of mineral oil is about 10% by weight, about 20% by weight, about 30% by weight, about 40% by weight, about 60% by weight, about 70% by weight, about 80% by weight, or about 90% by weight.
[0148] In some embodiments, the concentration of the acid is from about 20% to about 80% by weight, from about 30% to about 80% by weight, from about 40% to about 80% by weight, from about 50% to about 80% by weight, from about 60% to about 80% by weight, from about 70% to about 80% by weight, from about 20% to about 70% by weight, from about 30% to about 70% by weight, from about 40% to about 70% by weight, from about 50% to about 70% by weight, from about 60% to about 70% by weight, from about 20% to about 60% by weight, from about 30% to about 60% by weight, from about 40% to about 60% by weight, from about 50% to about 60% by weight, from about 20% to about 50% by weight, from about 30% to about 50% by weight, from about 40% to about 50% by weight, from about 20% to about 40% by weight, or from about 20% to about 30% by weight.
[0149] In some embodiments, the concentration of the acid is about 50% by weight. In some embodiments, the concentration of the acid is about 10% by weight, about 20% by weight, about 30% by weight, about 40% by weight, about 60% by weight, about 70% by weight, about 80% by weight, or about 90% by weight.
[0150] In some embodiments, the strength of the gel can be altered by the presence of one or more additives. In some embodiments, the gel strength is increased by the presence of one or more additives. In some embodiments, the gel strength is decreased by the presence of one or more additives. In some embodiments, the additive is a solid. In some embodiments, the additive is a polymer. The polymer can be a synthetic polymer or a biopolymer. In some embodiments, the additive is a drilling mud or a component of a drilling mud. Fig.25 As shown, the increase of drilling mud content in DBS gel leads to the increase of storage modulus in LVE region, indicating the increase of gel strength.
[0151] The above description of specific aspects will fully reveal the general nature of the present disclosure, that is, others can easily modify and / or adapt these specific aspects for various applications by applying technical knowledge in the field without undue experimentation and without departing from the general concept of the present disclosure.
[0152] Therefore, based on the teaching and guidance provided herein, these adaptations and modifications should be considered to be within the equivalent meaning and scope of the disclosed aspects. It should be understood that the words or terms in this article are used for descriptive purposes only, not for limiting purposes, and therefore the terms or words of this specification should be interpreted by those of ordinary skill in the art based on the teaching and guidance of the present disclosure.
[0153] The breadth and scope of the present disclosure should not be limited by any of the above-described exemplary aspects, but should be defined only in accordance with the following claims and their equivalents.
Claims
1. A self-degrading gel composition comprising a liquid, a gelling agent and a degradation agent, wherein the degradation agent degrades the gelling agent over time.
2. The self-degradable gel composition according to claim 1, wherein the gelling agent is a low molecular weight compound.
3. The self-degradable gel composition according to claim 1 or 2, wherein the gelling agent is dibenzylidene sorbitol (DBS), methyldibenzylidene sorbitol (methyl-DBS), dimethyldibenzylidene sorbitol (dimethyl-DBS), any other functional derivatives of dibenzylidene sorbitol, or a combination thereof.
4. The self-degradable gel composition according to any one of claims 1 to 3, wherein the gelling agent is DBS.
5. The self-degradable gel composition according to any one of claims 1 to 4, wherein the concentration of the gelling agent is from about 0.25 wt% to about 15 wt%.
6. The self-degradable gel composition of claim 5, wherein the concentration of the gelling agent is from about 0.25 wt% to about 5 wt%.
7. The self-degradable gel composition of claim 6, wherein the concentration of the gelling agent is about 2 wt% to about 4 wt%.
8. The self-degradable gel composition of claim 6, wherein the concentration of the gelling agent is about 0.25 wt%.
9. The self-degradable gel composition of claim 6, wherein the concentration of the gelling agent is about 0.5 wt%.
10. The self-degradable gel composition of claim 6, wherein the concentration of the gelling agent is about 1 wt%.
11. The self-degradable gel composition of claim 7, wherein the concentration of the gelling agent is about 2 wt%.
12. The self-degradable gel composition of claim 7, wherein the concentration of the gelling agent is about 3 wt%.
13. The self-degradable gel composition of claim 7, wherein the concentration of the gelling agent is about 4 wt%.
14. The self-degradable gel composition according to any one of claims 1 to 13, wherein the degradation agent comprises one or more acids.
15. The self-degradable gel composition of claim 14, wherein the one or more acids are inorganic acids, organic acids, Lewis acids or combinations thereof.
16. The self-degradable gel composition according to claim 15, wherein the inorganic acid is hydrochloric acid.
17. The self-degradable gel composition according to claim 15, wherein the organic acid is butyric acid, hexanoic acid, octanoic acid, decanoic acid, dodecanoic acid, citric acid, formic acid or a combination thereof.
18. The self-degradable gel composition according to claim 15, wherein the Lewis acid is aluminum (III) chloride or bismuth (III) trifluoromethanesulfonate.
19. The self-degradable gel composition according to any one of claims 1 to 18, wherein the self-degradable gel composition further comprises a solvent.
20. The self-degradable gel composition according to claim 19, wherein the solvent is dimethyl sulfoxide (DMSO), cyrene, dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP) or a combination thereof.
21. The self-degradable gel composition according to claim 20, wherein the solvent is DMSO.
22. The self-degradable gel composition according to claim 20 or 21, wherein a portion of the DMSO is encapsulated in wax particles.
23. The self-degradable gel composition according to any one of claims 1 to 22, wherein the liquid comprises an oil-based liquid or a water-based liquid.
24. The self-degradable gel composition of claim 23, wherein the oil-based liquid comprises mineral oil.
25. The self-degradable gel composition according to claim 23 or 24, wherein the liquid further comprises hexanol, an organic acid or a combination thereof.
26. The self-degradable gel composition of claim 24 or 25, wherein the liquid comprises about 20 wt% to about 80 wt% of mineral oil and about 20 wt% to about 80 wt% of hexanol, an organic acid, or a combination thereof.
27. The self-degradable gel composition of claim 26, wherein the liquid comprises about 30% to about 50% by weight of mineral oil and about 30% to about 50% by weight of hexanol.
28. A method for preventing fluid loss in a rock formation, comprising: The following steps are involved: injecting fluid into a borehole in a rock formation; and A plugging material is injected into the borehole, wherein the plugging material comprises a gelling agent, which is a gel that plugs fractures or pore spaces in the rock formation.
29. The method of claim 28, wherein the loss occurs before, during or after a drilling operation.
30. The method according to claim 28 or 29, wherein the plugging material is a lost circulation material.
31. The method of any one of claims 28-30, wherein the fluid is a drilling fluid.
32. The method of any one of claims 28-31, wherein the gelling agent gel is a self-degrading gel that degrades over time.
33. The method according to any one of claims 28 to 32, wherein the gelling agent is a self-degrading gel when it is partially gelled in the lower portion of the borehole.
34. The method of any one of claims 28-33, wherein the gelling agent is a low molecular weight compound.
35. The method of any one of claims 28-34, wherein the gelling agent is dibenzylidene sorbitol (DBS), methyldibenzylidene sorbitol (methyl-DBS), dimethyldibenzylidene sorbitol (dimethyl-DBS), any other functional derivative of dibenzylidene sorbitol, or a combination thereof.
36. The method of any one of claims 28-35, wherein the gelling agent is DBS.
37. The method of any one of claims 28-36, wherein the concentration of the gelling agent is from about 0.25 wt% to about 15 wt%.
38. The method of claim 37, wherein the concentration of the gelling agent is from about 0.25 wt% to about 5 wt%.
39. The method of claim 38, wherein the concentration of the gelling agent is from about 2% to about 4% by weight.
40. The method of claim 38, wherein the gelling agent has a concentration of about 0.25% by weight.
41. The method of claim 38, wherein the gelling agent has a concentration of about 0.5% by weight.
42. The method of claim 38, wherein the concentration of the gelling agent is about 1% by weight.
43. The method of claim 39, wherein the concentration of the gelling agent is about 2% by weight.
44. The method of claim 39, wherein the concentration of the gelling agent is about 3% by weight.
45. The method of claim 39, wherein the concentration of the gelling agent is about 4% by weight.
46. The method of any one of claims 28-45, wherein the plugging material further comprises a degradation agent.
47. The method of claim 46, wherein the degradation agent comprises one or more acids.
48. The method of claim 47, wherein the acid is an inorganic acid, an organic acid, a Lewis acid, or a combination thereof.
49. The method of claim 48, wherein the inorganic acid is hydrochloric acid.
50. The method of claim 48, wherein the organic acid is butyric acid, hexanoic acid, octanoic acid, decanoic acid, dodecanoic acid, citric acid, formic acid, or a combination thereof.
51. The method of claim 48, wherein the Lewis acid is aluminum (III) chloride or bismuth (III) trifluoromethanesulfonate.
52. The method of any one of claims 28-51, wherein the plugging material further comprises a solvent.
53. The method of claim 39, wherein the solvent is dimethyl sulfoxide (DMSO), cyrene, dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), or a combination thereof.
54. The method of claim 53, wherein the solvent is DMSO.
55. The method of claim 53 or 54, wherein a portion of the DMSO is encapsulated in wax particles.
56. The method of any one of claims 28-55, wherein the plugging material further comprises a liquid.
57. The method of claim 56, wherein the liquid comprises an oil-based liquid or a water-based liquid.
58. The method of claim 57, wherein the oil-based liquid comprises mineral oil.
59. The method of claim 57 or 58, wherein the liquid further comprises hexanol, an organic acid, or a combination thereof.
60. The method of claim 58 or 59, wherein the liquid comprises from about 20% to about 80% by weight of mineral oil and from about 20% to about 80% by weight of hexanol, an organic acid, or a combination thereof.
61. The method of claim 60, wherein the liquid comprises from about 30% to about 50% by weight mineral oil and from about 30% to about 50% by weight hexanol.
62. The method of any one of claims 28-61, wherein the gel is formed without heating.
63. The method of any one of claims 28-62, wherein the sealing of the fracture is reversible.
64. The method of claim 63, wherein the gel seals the fracture for about 1 day to about 16 weeks.
65. The method of claim 64, wherein the gel seals the fracture for about 2 weeks to about 6 weeks.
66. The method of any one of claims 63-65, wherein sealing of the fracture is reversed by degradation of the gel.
67. The method of any one of claims 28-66, wherein the fractures or pore spaces contain oil, brine, or other reservoir fluids.
68. The method of claim 67, wherein sealing of the fracture prevents the fluid from contacting the reservoir fluid.
69. The method of claim 67, wherein the fluid is not in contact with the reservoir fluid.
70. The method of claim 67, wherein the reservoir fluid is not contaminated by the drilling fluid.
71. A method of improving recovery of reservoir fluids from fractures or pore spaces comprising plugging the fractures or pore spaces with the self-degradable gel composition of any one of claims 1-27.
